Narratives of success and narratives of failure: representations of the career of King Hugh of Italy (c.885-948) - Balzaretti, Ross (Wiley, 2016)
Hugh of Arles, King of Italy between 926 and 947, has come to be regarded as one of the more successful kings of Italy in the tenth century. The evidence of his charters supports this conclusion, showing how effectively he managed to insert members of his own Provençal family into the existing political fabric of northern Italy. Contemporary narrative sources tell the same story but as one of failure. For Rather of Verona, Liutprand of Cremona and even Flodoard of Reims, Hugh and his family were suspect and their sexual mores questionable. Their texts intervened in contemporary politics not simply as records of Hugh’s inadequacies but as real political actors which helped to make that failure happen.